Changes in chemical constituents and overall acceptability of papaya jam fortified with soya protein during storage - Dimas Bayu PINANDOYO; Arisadi MASNAR (E-Journal Menara Perkebunan, 2020)
Processed fruit products commonly contain very low protein due to the heat treatment during processing period. This article presents the researchresults concerning the increase of nutrition value of papaya jam fortified with soya protein concentrate. Papaya jam prepared with ratio 40:1, 40:2, 40:3, 40:4, and 40:5 (v/v) of papaya pulp and soya protein concentrate. The treatment of papaya jam and soya protein with the highest acceptability was then analyzed for the changes in chemical constituents and overall acceptability at monthly interval during three months of storage. The parameters that being analyzed were moisture content, total soluble solids (TSS), pH, total and reducing sugars, non-enzymatic browning, acidity, ascorbic acid, total carotenoid, total phenol, crude protein, and total plate count.  The results showed that fortified papaya jams prepared with papaya pulp and soy protein concentrate ratio at 40:1 had the highest acceptability. During storage time it revealed that moisture content, TSS, pH, total and reducing sugars, and non-enzymatic browning increased, while acidity, ascorbic acid, total carotenoids, phenols, total antioxidants and crude protein contents of jam decreased. Fortification of papaya jam with soya protein concentrate (40:1 v/v) increased crude protein content on average from 3.15% to 4.16%. Total plate count (TPC) indicated that no microbial contamination during 3 months storage period. It can be concluded that papaya jam fortified with soya protein concentrate remained acceptable during storage although the acceptability decreased over time.